Cerebral metabolism and vascular reactivity during breath-hold and hypoxic challenge in freedivers and healthy controls. Issue 5 (May 2019) - Vestergaard, Mark B; Larsson, Henrik BW
The goal of the present study was to examine the cerebral metabolism and vascular reactivity during extended breath-holds (ranging from 2 min 32 s to 7 min 0 s) and during a hypoxic challenge in freedivers and non-diver controls. Magnetic resonance imaging was used to measure the global cerebral blood flow (CBF) and metabolic rate of oxygen (CMRO2 ), and magnetic resonance spectroscopy was used to measure the cerebral lactate, glutamate+glutamine, N-acetylaspartate and phosphocreatine+creatine concentrations in the occipital lobe. Fifteen freedivers and seventeen non-diver controls participated. The freedivers showed remarkable increases in CBF (107%) during the breath-holds, compensating for arterial desaturation, and sustained cerebral oxygen delivery (CDO2 ). CMRO2 was unaffected throughout the breath-holds. During the hypoxic challenge, the freedivers had larger increases in blood flow in the sagittal sinus than the non-divers, and could sustain normal CDO2 . No differences were found in lactate production, global CBF or CMRO2 . We conclude that the mechanism for sustaining brain function during breath-holding in freedivers involves an extraordinary increase in perfusion, and that freedivers present evidence for higher cerebrovascular reactivity, but not for higher lactate-producing glycolysis during a hypoxic challenge compared to controls.